To find the two unknown angle measures that form the 90° angle, we can set up an equation using the fact that the sum of adjacent angles is equal to 90°.
Let's say the two unknown angle measures are (x+4)° and (3x+2)°.
According to the given information, the sum of these two angles is 90°.
So, the equation we can set up is:
(x+4)° + (3x+2)° = 90°
To solve this equation, we combine like terms:
4x + 6 = 90
Next, we isolate the variable:
4x = 90 - 6
4x = 84
Finally, we solve for x by dividing both sides of the equation by 4:
x = 84/4
x = 21
Now that we know the value of x, we can substitute it back into the original expressions to find the angle measures:
(x+4)° = 21 + 4 = 25°
(3x+2)° = 3(21) + 2 = 63 + 2 = 65°
Therefore, the two unknown angle measures that form the 90° angle are 25° and 65°.
Solve Equations with Adjacent Angles Practice%0D%0AComplete this assessment to review what you've learned. It will not count toward your grade.%0D%0A5 of 55 of 5 Items%0D%0A%0D%0A%0D%0A%0D%0A%0D%0A%0D%0A%0D%0AQuestion%0D%0AUse the image to answer the question.%0D%0A%0D%0AAn illustration shows three rays extending from a common origin. The angle measures between them are labeled.%0D%0A%0D%0AWhat are the two unknown angle measures that form the 90°%0D%0A90%0D%0A°%0D%0A angle?%0D%0A%0D%0A(1 point)%0D%0A(x+4)°=%0D%0A(%0D%0A%0D%0A+%0D%0A4%0D%0A)%0D%0A°%0D%0A=%0D%0A °%0D%0A°%0D%0A, (3x+2)°=%0D%0A(%0D%0A3%0D%0A%0D%0A+%0D%0A2%0D%0A)%0D%0A°%0D%0A=%0D%0A °
1 answer